Exploring the views of undocumented migrant women on access to maternity services in the UK. (30th September 2020) - Hargreaves, S; Nellums, L B; Powis, J; Jones, L; Miller, A; Rustage, K; Russell, N; Friedland, J
Abstract: Background: Migrant women face inequalities in access to health-care services and are known to experience poorer maternal and child outcomes than women born in the UK. The development of more restrictive health policies in the UK and Europe, including being denied or charged for healthcare at maternity services, may be exacerbating these outcomes, particularly among undocumented migrant women without permission to reside. We investigated undocumented migrant women's experiences of accessing maternity services in the UK and their impact on health outcomes. Methods: We did semi-structured in-depth qualitative interviews with a purposive sample of migrant women (born outside the UK) who were aged 18 and over, and had experiences of pregnancy in the UK whilst undocumented. Participants were recruited through the Doctors of the World UK clinic. Interviews were transcribed and analysed using thematic analysis. Results: We did interviews with 20 undocumented women (age range 31-40 years; mainly from Africa and Asia). Among participants, of whom 13 were pregnant at the time of interview, 10 (50%) first accessed antenatal care late (after the national target of 13 weeks). Women described an ongoing cycle of precariousness, defined by their legal status, social isolation, and poor economic status. Women reported receiving bills of up to £11, 500 for maternity services (range £3, 072 to £11.500). The impact of their experiences meant that they were deterred from seeking timely health care and were reluctant to present to health services, with women reporting fear and loss of trust in the health system. Conclusions: These women's narratives illustrated the potential deterrent and detrimental impact of increasingly restrictive health policies on women's access to care and their health. UK and European health policies must be equitable, non-discriminatory, and better align with our commitments to promote universal health coverage among all individual residing in the region. Key messages: Increasingly restrictive health policies may have a deterrent and detrimental impact on migrant women's access to health care. Undocumented migrant women in the UK reported fear and loss of trust in the health system.